2002
DOI: 10.1152/physrev.00028.2001
|View full text |Cite
|
Sign up to set email alerts
|

Function and Genetics of Dystrophin and Dystrophin-Related Proteins in Muscle

Abstract: The X-linked muscle-wasting disease Duchenne muscular dystrophy is caused by mutations in the gene encoding dystrophin. There is currently no effective treatment for the disease; however, the complex molecular pathology of this disorder is now being unravelled. Dystrophin is located at the muscle sarcolemma in a membrane-spanning protein complex that connects the cytoskeleton to the basal lamina. Mutations in many components of the dystrophin protein complex cause other forms of autosomally inherited muscular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
899
2
40

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,052 publications
(958 citation statements)
references
References 511 publications
(448 reference statements)
17
899
2
40
Order By: Relevance
“…Utrophin upregulation does occur in some mdx myofibers, particularly in regenerating myofibers in younger mdx animals [3,35,36]. Indeed, some of our early experiments with AAV2-Galgt2, which yielded far fewer infected myofibers on a vg basis than our later experiments with AAV1-Galgt2, showed that some utrophin upregulation did occur in some Galgt2 overexpressing myofibers.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Utrophin upregulation does occur in some mdx myofibers, particularly in regenerating myofibers in younger mdx animals [3,35,36]. Indeed, some of our early experiments with AAV2-Galgt2, which yielded far fewer infected myofibers on a vg basis than our later experiments with AAV1-Galgt2, showed that some utrophin upregulation did occur in some Galgt2 overexpressing myofibers.…”
Section: Discussionmentioning
confidence: 65%
“…mdx mice are a commonly used model for testing therapeutic approaches to DMD; mdx animals do not express dystrophin protein in most of their skeletal myofibers, and mdx myofibers exhibit several important pathological hallmarks of DMD [3,4]. In addition, loss of dystrophin protein expression, both in DMD and mdx muscles, correlates with loss of membrane expression of proteins in the dystrophin-glycoprotein complex, including dystroglycans and sarcoglycans, along the myofiber membrane [5].…”
Section: Introductionmentioning
confidence: 99%
“…While studies of mdx mice have greatly advanced our understanding of dystrophinopathies in humans, there are a number of important pathological differences between dystrophindeficient humans and mice. Furthermore, mutations in genes encoding other DGC components or associated proteins have been implicated in clinically distinct forms of muscular dystrophy [2,3]. Finally, the complexity of the costameric protein network supports the hypothesis that additional proteins may form distinct mechanical linkages parallel to the DGC γ cyto -actin axis.…”
Section: Introductionmentioning
confidence: 75%
“…Utrophin is upregulated in both animals [37][38][39][40] suggesting that a similar compensatory remodeling program is activated in dystrophindeficient mice and dogs. However, GRMD dogs suffer a severe and rapidly progressing muscle disease with premature lethality more closely resembling DMD in humans while mdx mice exhibit a milder phenotype with no dramatic reduction in lifespan [3]. Thus, it appears that compensatory cytoskeletal remodeling is not as effective in dystrophin-deficient dogs compared to mice, which may be due to the greater mechanical stresses imposed on the sarcolemma of larger animals with correspondingly larger myofibers [30,41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation